DAKWAH DAN KOMUNIKASI Jurusan Dakwah STAIN Purwokerto KOMUNIKA ISSN: 1978-1261 Vol.3 No.2 Juli-Desember 2009 pp.255-269 DAKWAHTAINMENT: KOMODIFIKASI INDUSTRI MEDIA DI BALIK AYAT TUHAN - Aris Saefulloh (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2009)
Dakwahtainment is a product of broadcasting media industry as a religious program to serve people’sspirituality need. In dakwahtainment, dakwah message and juru dakwah become a commodity and part of popularculture products. Possible, this is a realization of method and creative media for dakwah itself or as post-fordist of mediaindustry (television) by observe market’s need and interest, based on certain moment. But if seen from critical perspective,there’s exploitation to God’s verses and its representation as religion, become content of media industry. Religious mattersexploited as commodity in media industry. Therefore, there’s existed symbiosis-mutualism, with most gain at media, andconsumer only get spiritual satisfaction and religious information.